IMPLIKASI PERNIKAHAN DINI TERHADAP POLA ASUH ANAK: STUDI KASUS DI DESA SUMBERPINANG KABUPATEN JEMBER - Kusuma Wiranata; Winning Son Ashari (USRAH: Jurnal Hukum Keluarga Islam, 2025)
Early marriage remains a social reality in several rural areas of Indonesia, including Sumberpinang Village, Pakusari District, Jember Regency. Parenting in early-married families tends to be less optimal due to unbalanced caregiving roles, limited attention to children’s needs, and the lack of emotional readiness among young parents. This study aims to examine the implications of early marriage on parenting using a qualitative case study approach involving couples who married before the age of 19. Data were collected through in-depth interviews, limited observation, and documentation, then analyzed interactively using the Miles, Huberman, and Saldaña model. The findings indicate that early marriage leads to neglectful and authoritarian parenting styles, while democratic parenting is rarely found and permissive parenting was not identified. These conditions are closely related to economic instability, limited parenting knowledge, and the intergenerational transmission of early marriage practices. As a result, children are at risk of neglect, lack emotional support, face stunting, and grow up with fear and low self-confidence. This study contributes academically by enriching the literature on the relationship between rural cultural structures and parenting practices among young families. Practically, it provides a foundation for interventions such as parenting education, economic empowerment, and reproductive health literacy to improve parenting quality and break the cycle of early marriage in rural communities